FENOMENA CYBER PIRACY BERBASIS INSTAGRAM DI MAN 2 PONOROGO - Ela Rohmawati; Asmah Rohma Fatul Fauziah; Cindy Marcella; Arzeti Ulul Hamidah; Nurul Malikah (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2022)
This study aims to determine the phenomenon of cyberpiracy based on Instagram at MAN 2 Ponorogo. This study uses a qualitative approach; the type of research is descriptive analysis with data collection techniques in the form of interviews. The subjects in this study were 30 students at MAN 2 Ponorogo who were active users of Instagram. Most of them are users of the "Add Yours" feature on the Instagram application. The results of this study are that 96.7% of the negative impacts of using the Instagram application were found, and 30% of students had used this feature due to a lack of understanding of cyber piracy. The negative impact is the Add Yours feature which is a form of cyber piracy crime. Students use this feature only to follow trends. However, after students know this, they no longer use this feature. The formation of morals in today's young generation is needed to limit themselves in dealing with various problems that exist both in the real world and the virtual world.